Micro-porous concrete for ecological sea embankment and preparation method thereof

CN123026408APending Publication Date: 2026-11-03GUANGZHOU URBAN PLANNING & DESIGN SURVEY RES INST
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611182512.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-05
Publication Date
2026-11-03

AI Technical Summary

Technical Problem

Existing microporous concrete used for ecological seawalls cannot simultaneously meet the dual requirements of high porosity to meet the attachment needs of marine organisms and high mechanical strength to resist wind and wave impact and seawater erosion, resulting in a difficulty in balancing structural stability and ecological function.

Method used

Modified hydroxyapatite and cetearyl glucoside are used. The modified hydroxyapatite tightly binds the pore interface, improving porosity and bonding strength. The cetearyl glucoside optimizes the pore interface environment, and the combination with polypropylene fibers enhances the stability of the pore structure.

Benefits of technology

The microporous concrete achieves a porosity that meets the needs of marine organism attachment and water exchange, while improving compressive and flexural strength to resist the impact of wind and waves and seawater erosion faced by the seawall.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The application provides a kind of microporous concrete for sea embankment ecologicalization and a preparation method thereof, and belongs to the technical field of concrete.The microporous concrete of the application comprises the following components by weight: cement 60-90 parts, fly ash 20-30 parts, coarse aggregate 100-150 parts, fine aggregate 180-200 parts, cetyl stearyl glucoside 0.1-0.5 parts, modified hydroxyapatite 3-10 parts, foaming agent 0.5-0.8 parts, air entraining agent 0.01-0.024 parts, and water 45-60 parts.The modifier of the modified hydroxyapatite comprises tannic acid.The microporous concrete of the application has high porosity and mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of concrete technology, specifically to microporous concrete for the ecologicalization of seawalls and its preparation method. Background Technology

[0002] In seawall construction, with the advancement of ecological and environmental protection concepts, the ecologicalization of seawalls has become an important development direction. Microporous concrete, due to its porous structure, biocompatibility, and ease of application, has become one of the key materials for the ecological construction of seawalls. Seawalls are situated in unique environments, constantly facing complex conditions such as seawater immersion, salt spray erosion, and wave impact. This places dual core requirements on microporous concrete: firstly, it must possess sufficient porosity to meet the needs of marine organisms (such as shellfish, algae, and other benthic organisms) for attachment and to facilitate water infiltration and exchange. Typically, a total porosity of no less than 35% is required, with uniform pore size distribution to avoid impacting habitats due to excessively large or small pores; secondly, it must possess good mechanical strength to withstand the loads generated by wave impact and structural deterioration caused by seawater erosion, ensuring the stability of the seawall structure. Existing microporous concrete used for ecological seawalls often faces the problem of balancing porosity and strength: if high porosity is pursued to meet the needs of marine organism attachment and water exchange, it will easily lead to a decrease in concrete strength, making it unable to resist seawater erosion and the impact of wind and waves; if strength is emphasized, the porosity will decrease, resulting in the loss of ecological function. This contradiction has become a key bottleneck restricting the promotion and application of microporous concrete. Summary of the Invention

[0003] The purpose of this application is to overcome the shortcomings of the prior art and provide a microporous concrete for the ecologicalization of seawalls and its preparation method.

[0004] To achieve the above objectives, the technical solution adopted in this application is as follows: In the first aspect, a microporous concrete is provided, comprising the following components in parts by weight: 60-90 parts cement, 20-30 parts fly ash, 100-150 parts coarse aggregate, 180-200 parts fine aggregate, 0.1-0.5 parts cetearyl glucoside, 3-10 parts modified hydroxyapatite, 0.5-0.8 parts foaming agent, 0.01-0.024 parts air-entraining agent, and 45-60 parts water; The modifier of the modified hydroxyapatite includes tannic acid.

[0005] In some embodiments, the method for preparing the modified hydroxyapatite includes the following steps: Hydroxyapatite was added to an aqueous solution of tannic acid, and the pH was adjusted to 8-8.5 with a pH adjuster. The mixture was stirred at 40-60℃ for 2-4 hours. The product obtained from the reaction was filtered, washed, and dried to obtain modified hydroxyapatite. The mass-volume ratio of hydroxyapatite to the aqueous solution of tannic acid was 1 g: (50-100) mL.

[0006] In some embodiments, the modifier of the modified hydroxyapatite further includes sodium silicate; the preparation method of the modified hydroxyapatite includes the following steps: Hydroxyapatite was added to an aqueous solution of tannic acid, and the pH was adjusted to 8-8.5 with a pH adjuster. The mixture was stirred and reacted at 40-60℃ for 2-4 hours. The product obtained from the reaction was filtered, washed, and dried to obtain tannic acid-modified hydroxyapatite. Tannic acid-modified hydroxyapatite was added to an aqueous solution of sodium silicate and stirred at 25-40°C for 1-2 hours. The pH was adjusted to 6.0-7.0 with a pH adjuster, and the reaction was continued for 1-2 hours. The product obtained from the reaction was filtered, washed, and dried to obtain modified hydroxyapatite. The mass-to-volume ratio of hydroxyapatite to tannic acid aqueous solution is 1 g: (50-100) mL. The mass-to-volume ratio of tannic acid-modified hydroxyapatite and sodium silicate aqueous solution is 1 g: (30-60) mL.

[0007] In some embodiments, the modifier of the modified hydroxyapatite further includes a silane coupling agent; the preparation method of the modified hydroxyapatite includes the following steps: Hydroxyapatite was added to an aqueous solution of tannic acid, and the pH was adjusted to 8-8.5 with a pH adjuster. The mixture was stirred and reacted at 40-60℃ for 2-4 hours. The product obtained from the reaction was filtered, washed, and dried to obtain tannic acid-modified hydroxyapatite. Tannic acid-modified hydroxyapatite was added to an aqueous solution of sodium silicate and stirred at 25-40°C for 1-2 hours. After adjusting the pH to 6-7 with a pH adjuster, the reaction was continued for 1-2 hours. Then, a first silane coupling agent solution was added and the reaction was stirred at 25-40°C for 0.5-1 hours. The product obtained from the reaction was filtered, washed, and dried to obtain modified hydroxyapatite. The mass-to-volume ratio of hydroxyapatite to tannic acid aqueous solution is 1 g: (50-100) mL. The mass-to-volume ratio of tannic acid-modified hydroxyapatite and sodium silicate aqueous solution is 1 g: (30-60) mL; The mass of the first silane coupling agent is 5-15% of the mass of sodium silicate.

[0008] In some embodiments, the first silane coupling agent is at least one of an aminosilane coupling agent and an epoxysilane coupling agent; In some embodiments, the first silane coupling agent solution is prepared by adding the first silane coupling agent to an ethanol / water solution, adjusting the pH to 4-5 with a pH adjuster, and stirring at 25-35°C for 30-40 minutes to obtain the first silane coupling agent solution, wherein the volume ratio of ethanol to water is 1:(5-10).

[0009] In some embodiments, the cetearyl glucoside has a coating layer on its surface, the coating layer comprising polyethylene glycol diacrylate and chitosan.

[0010] In some embodiments, the microporous concrete includes polypropylene fibers in the form of 0.5 to 2.5 parts by weight.

[0011] In some implementations, at least one of the following (1)-(5) is satisfied: (1) The coarse aggregate is granite crushed stone and / or basalt crushed stone with an average particle size of 5-10 mm; (2) The fine aggregate is quartz sand with an average particle size of 1-2 mm; (3) The foaming agent is a protein-based foaming agent; (4) The air-entraining agent is a rosin thermal polymer air-entraining agent; (5) The cement is silicate cement.

[0012] Secondly, a method for preparing the aforementioned microporous concrete is provided, comprising the following steps: Cement, fly ash, coarse aggregate, fine aggregate, and modified hydroxyapatite powder are mixed evenly to obtain a dry mixture; Add cetearyl glucoside, air-entraining agent and water to the dry mixture, stir well to obtain slurry; Foam is obtained by foaming with a foaming agent; Add foam to the slurry and stir evenly to obtain microporous concrete.

[0013] In some embodiments, the step of adding foam to the slurry is as follows: The foam is divided into a first foam and a second foam, with the volume of the first foam being 60-70% of the total foam volume. The second foam and the second silane coupling agent are mixed evenly to obtain the third foam; wherein the mass of the second silane coupling agent is 0.5-1% of the mass of the foam. Add the first foam to the slurry and stir evenly. Then add the third foam at a temperature of 20-35℃ and stir evenly to obtain microporous concrete.

[0014] Compared with the prior art, the beneficial effects of this application are as follows: The microporous concrete of this application incorporates cetearyl glucoside and modified hydroxyapatite. Cetearyl glucoside optimizes the pore interface environment, providing a stable adhesion base for the modified hydroxyapatite. The tannic acid-modified hydroxyapatite can tightly bind to the pore interface, which not only reduces the collapse and merging of pores during curing and increases the porosity of the microporous concrete, but also enhances the bonding strength between the pores and the microporous concrete matrix, thereby improving the mechanical properties of the microporous concrete. This allows the porosity of the microporous concrete to meet the ecological needs of marine organism attachment and water exchange, while the compressive strength and flexural strength of the microporous concrete can withstand the impact of wind and waves and seawater erosion faced by the seawall. Detailed Implementation

[0015] To facilitate understanding of this application, a more complete description will be provided below. However, this application can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a more thorough and complete understanding of the disclosure of this application.

[0016] As used in this article: "Prepared from" is synonymous with "comprising". The terms "comprising", "including", "having", "containing", or any other variations thereof as used herein are intended to cover non-exclusive inclusion. For example, a composition, step, method, article, or apparatus that includes the listed elements is not necessarily limited to those elements, but may include other elements not expressly listed or elements inherent to such composition, step, method, article, or apparatus.

[0017] The conjunction "composed of..." excludes any unspecified elements, steps, or components. If used in a claim, this phrase makes the claim closed, excluding materials other than those described, except for associated conventional impurities. When the phrase "composed of..." appears in a clause of the body of a claim rather than immediately following it, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.

[0018] When a quantity, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pair of any upper or preferred value with any lower or preferred value, regardless of whether the range is disclosed individually. For example, when the range “1-5” is disclosed, the described range should be interpreted as including ranges “1-4”, “1-3”, “1-2”, “1-2 and 4-5”, “1-3 and 5”, etc. When numerical ranges are described herein, unless otherwise stated, the range is intended to include its endpoints and all integers and fractions within that range.

[0019] In these embodiments, unless otherwise specified, the portions and percentages are all by weight.

[0020] "Parts by mass" refers to the basic unit of measurement that expresses the mass ratio of multiple components. One part can represent any unit mass, such as 1g or 2.689g. If we say that component A has 'a' parts by mass and component B has 'b' parts by mass, it means that the mass ratio of component A to component B is a:b. It is important to understand that, unlike mass percentage content, the sum of the mass parts of all components is not limited to 100 parts.

[0021] "And / or" is used to indicate that one or both of the described situations may occur, for example, A and / or B includes (A and B) and (A or B).

[0022] In a first aspect, a microporous concrete is provided, comprising the following components in parts by weight: 60-90 parts cement, 20-30 parts fly ash, 100-150 parts coarse aggregate, 180-200 parts fine aggregate, 0.1-0.5 parts cetearyl glucoside, 3-10 parts modified hydroxyapatite, 0.5-0.8 parts foaming agent, 0.01-0.024 parts air-entraining agent, and 45-60 parts water; The modifier of the modified hydroxyapatite includes tannic acid.

[0023] The microporous concrete of this application incorporates cetearyl glucoside and modified hydroxyapatite. Cetearyl glucoside optimizes the pore interface environment, providing a stable adhesion base for the modified hydroxyapatite. The tannic acid-modified hydroxyapatite can tightly bind to the pore interface, which not only reduces the collapse and merging of pores during curing, increasing the porosity of the microporous concrete, but also enhances the bonding strength between the pores and the microporous concrete matrix, improving the mechanical properties of the microporous concrete. This allows the porosity of the microporous concrete to meet the ecological needs of marine organism attachment and water exchange, while the compressive and flexural strengths of the microporous concrete can withstand the impact of wind and waves and seawater erosion faced by seawalls.

[0024] Specifically, the weight parts of cement can be a range of 60 parts, 62 parts, 65 parts, 67 parts, 70 parts, 73 parts, 75 parts, 78 parts, 80 parts, 82 parts, 85 parts, 87 parts, or 90 parts, or any combination of both.

[0025] Specifically, the weight parts of fly ash can be a range of 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts, 26 parts, 27 parts, 28 parts, 29 parts, or 30 parts, or any combination of both.

[0026] Specifically, the weight parts of coarse aggregate can be a range of one or any two of the following: 100 parts, 105 parts, 110 parts, 115 parts, 120 parts, 125 parts, 130 parts, 135 parts, 140 parts, 145 parts, and 150 parts.

[0027] Specifically, the weight parts of fine aggregate can be a range of one or any two of the following: 180 parts, 182 parts, 184 parts, 186 parts, 188 parts, 190 parts, 192 parts, 194 parts, 196 parts, 198 parts, and 200 parts.

[0028] Specifically, the weight parts of cetearyl glucoside can be one or any combination of 0.1 parts, 0.15 parts, 0.2 parts, 0.25 parts, 0.3 parts, 0.35 parts, 0.4 parts, 0.45 parts, and 0.5 parts.

[0029] Specifically, the weight parts of modified hydroxyapatite can be one or any combination of two of the following: 3 parts, 3.5 parts, 4 parts, 4.5 parts, 5 parts, 5.5 parts, 6 parts, 6.5 parts, 7 parts, 7.5 parts, 8 parts, 8.5 parts, 9 parts, 9.5 parts, and 10 parts.

[0030] Specifically, the weight parts of the foaming agent can be one or any combination of 0.5 parts, 0.52 parts, 0.55 parts, 0.57 parts, 0.6 parts, 0.63 parts, 0.65 parts, 0.68 parts, 0.7 parts, 0.72 parts, 0.75 parts, 0.77 parts, and 0.8 parts.

[0031] Specifically, the weight parts of the air-entraining agent can be one or any combination of 0.01 parts, 0.012 parts, 0.014 parts, 0.016 parts, 0.018 parts, 0.02 parts, 0.022 parts, and 0.024 parts.

[0032] Specifically, the weight parts of water can be a range of 45 parts, 47 parts, 49 parts, 51 parts, 53 parts, 55 parts, 58 parts, 60 parts, or any combination of both.

[0033] In some embodiments, the method for preparing the modified hydroxyapatite includes the following steps: Hydroxyapatite was added to an aqueous solution of tannic acid, and the pH was adjusted to 8-8.5 with a pH adjuster. The mixture was stirred at 40-60℃ for 2-4 hours. The product obtained from the reaction was filtered, washed, and dried to obtain modified hydroxyapatite. The mass-volume ratio of hydroxyapatite to the aqueous solution of tannic acid was 1 g: (50-100) mL.

[0034] Specifically, the mass-volume ratio of hydroxyapatite and tannic acid aqueous solution can be one of the following or any combination of two: 1g:50mL, 1g:55mL, 1g:60mL, 1g:65mL, 1g:70mL, 1g:75mL, 1g:80mL, 1g:85mL, 1g:90mL, 1g:95mL, 1g:100mL.

[0035] Specifically, the mass concentration of the tannic acid aqueous solution is 1-5 mg / mL, for example, it can be one or any combination of 1 mg / mL, 1.5 mg / mL, 2 mg / mL, 2.5 mg / mL, 3 mg / mL, 3.5 mg / mL, 4 mg / mL, 4.5 mg / mL, 5 mg / mL.

[0036] In some embodiments, the modifier of the modified hydroxyapatite further includes sodium silicate; the preparation method of the modified hydroxyapatite includes the following steps: Hydroxyapatite was added to an aqueous solution of tannic acid, and the pH was adjusted to 8-8.5 with a pH adjuster. The mixture was stirred and reacted at 40-60℃ for 2-4 hours. The product obtained from the reaction was filtered, washed, and dried to obtain tannic acid-modified hydroxyapatite. Tannic acid-modified hydroxyapatite was added to an aqueous solution of sodium silicate and stirred at 25-40°C for 1-2 hours. The pH was adjusted to 6.0-7.0 with a pH adjuster, and the reaction was continued for 1-2 hours. The product obtained from the reaction was filtered, washed, and dried to obtain modified hydroxyapatite. The mass-to-volume ratio of hydroxyapatite to tannic acid aqueous solution is 1 g: (50-100) mL. The mass-to-volume ratio of tannic acid-modified hydroxyapatite and sodium silicate aqueous solution is 1 g: (30-60) mL.

[0037] In this application, hydroxyapatite is modified sequentially with tannic acid and sodium silicate, which can increase the surface activity of hydroxyapatite and improve the interfacial compatibility between modified hydroxyapatite and the microporous concrete matrix and pores, thereby improving the porosity and mechanical properties of microporous concrete.

[0038] Specifically, the mass-volume ratio of tannic acid-modified hydroxyapatite and sodium silicate aqueous solution can be one of the following or any combination of two: 1g:30mL, 1g:35mL, 1g:40mL, 1g:45mL, 1g:50mL, 1g:55mL, 1g:60mL.

[0039] In some embodiments, the molar concentration of the sodium silicate aqueous solution is 0.1-0.5 mol / L, for example, it can be a range of one or any combination of 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L.

[0040] In some embodiments, the modifier of the modified hydroxyapatite further includes a silane coupling agent; the preparation method of the modified hydroxyapatite includes the following steps: Hydroxyapatite was added to an aqueous solution of tannic acid, and the pH was adjusted to 8-8.5 with a pH adjuster. The mixture was stirred and reacted at 40-60℃ for 2-4 hours. The product obtained from the reaction was filtered, washed, and dried to obtain tannic acid-modified hydroxyapatite. Tannic acid-modified hydroxyapatite was added to an aqueous solution of sodium silicate and stirred at 25-40°C for 1-2 hours. After adjusting the pH to 6-7 with a pH adjuster, the reaction was continued for 1-2 hours. Then, a first silane coupling agent solution was added and the reaction was stirred at 25-40°C for 0.5-1 hours. The product obtained from the reaction was filtered, washed, and dried to obtain modified hydroxyapatite. The mass-to-volume ratio of hydroxyapatite to tannic acid aqueous solution is 1 g: (50-100) mL. The mass-to-volume ratio of tannic acid-modified hydroxyapatite and sodium silicate aqueous solution is 1 g: (30-60) mL; The mass of the first silane coupling agent is 5-15% of the mass of sodium silicate.

[0041] In this application, hydroxyapatite is modified with tannic acid, and then further modified with sodium silicate and silane coupling agent. This allows for the construction of an optimized interface layer on the surface of hydroxyapatite, which enhances the bonding force between the modified hydroxyapatite and the microporous concrete matrix and the pore interface, reduces pore defects, and improves the porosity and mechanical properties of the microporous concrete.

[0042] Specifically, the mass of the first silane coupling agent can be a range of one or any two of the following: 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, and 15% of the mass of sodium silicate.

[0043] In this application, based on the mass of sodium silicate, the mass percentage of the first silane coupling agent is within the above-mentioned range, which is beneficial to improving the porosity and mechanical properties of microporous concrete.

[0044] In some embodiments, the first silane coupling agent is at least one of an aminosilane coupling agent and an epoxysilane coupling agent.

[0045] The first silane coupling agent in this application is within the aforementioned range and, in synergy with sodium silicate, constructs an "inorganic-organic" gradient covalent bonded interface layer on the surface of tannic acid-coated hydroxyapatite. This interface layer not only significantly improves the chemical compatibility and anchoring force between the modified hydroxyapatite and the cement matrix and pore walls, but also forms a dual protection of ion shielding and stress buffering at the pore interface, thereby effectively inhibiting the penetration of seawater erosion media and interface delamination under wet-dry cycles.

[0046] Specifically, the aminosilane coupling agent can be at least one of γ-aminopropyltriethoxysilane and γ-aminopropylmethyldiethoxysilane.

[0047] Specifically, the epoxy silane coupling agent can be at least one of 3-glycidyl etheroxypropyltrimethoxysilane and γ-(2,3-epoxypropoxy)propyltrimethoxysilane.

[0048] In some embodiments, the first silane coupling agent solution is prepared by adding the first silane coupling agent to an ethanol / water solution, adjusting the pH to 4-5 with a pH adjuster, and stirring at 25-35°C for 30-40 minutes to obtain the silane coupling agent solution, wherein the volume ratio of the first silane coupling agent to the ethanol / water solution is 1:(5-10); and the volume percentage of ethanol in the ethanol / water solution is 40-60%.

[0049] In this application, the first silane coupling agent solution prepared by the above method can activate the first silane coupling agent, improve the bonding effect between the first silane coupling agent and tannic acid modified hydroxyapatite, and further improve the bonding force between the modified hydroxyapatite and the microporous concrete matrix and the pore interface.

[0050] Specifically, the volume ratio of the first silane coupling agent to the ethanol / water solution can be one of or any combination of two of the following: 1:5, 1:5.5, 1:6, 1:6.5, 1:7, 1:7.5, 1:8, 1:8.5, 1:9, 1:9.5, 1:10.

[0051] Specifically, the volume percentage of ethanol in the aqueous ethanol solution can be a range of 40%, 42%, 44%, 46%, 48%, 50%, 52%, 54%, 56%, 58%, 60%, or any combination of two of these values.

[0052] In some embodiments, the pH adjuster is one of sodium hydroxide aqueous solution, dilute hydrochloric acid, or dilute sulfuric acid; those skilled in the art can choose according to the actual situation.

[0053] In some embodiments, the surface of the cetearyl glucoside is provided with a coating layer comprising polyethylene glycol diacrylate and chitosan.

[0054] By applying a coating layer to the surface of cetearyl glucoside, premature foaming loss of cetearyl glucoside during the mixing process of microporous concrete can be avoided, allowing it to continue to interact with modified hydroxyapatite, maintaining the stability of the pore structure, and thus improving the porosity and mechanical properties of microporous concrete.

[0055] It should be noted that when a coating layer is applied to the surface of cetearyl glucoside, the amount added to the microporous concrete is based on the weight of cetearyl glucoside.

[0056] In some embodiments, the method for preparing the coating layer on the surface of cetearyl glucoside can refer to the method for preparing microcapsules; for example, using cetearyl glucoside as the core material and polyethylene glycol diacrylate and chitosan as the wall material, cetearyl glucoside microcapsules are prepared with microwave assistance.

[0057] Specifically, the mass ratio of polyethylene glycol diacrylate to chitosan is (3:1) to (1:3); for example, it can be a range of values ​​consisting of one or any two of 3:1, 2:1, 1:1, 1:2, 1:3.

[0058] Specifically, the mass ratio of the core material to the wall material is 1:(6-10), for example, it can be one of 1:6, 1:7, 1:8, 1:9, 1:10 or any combination of both.

[0059] Specifically, the average particle size of the cetearyl glucoside microcapsules is 1-10 μm, for example, it can be one or any combination of 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm.

[0060] Specifically, the method for preparing the coating layer on the surface of the cetearyl glucoside includes the following steps: Cetearyl glucoside is heated and melted to form a core material solution; After dissolving chitosan in an aqueous acetic acid solution, polyethylene glycol diacrylate and ammonium persulfate are added and stirred until homogeneous to form a wall material solution. The core material solution was added dropwise to the wall material solution and then cured by irradiation to obtain cetearyl glucoside microcapsules.

[0061] Specifically, the mass percentage of acetic acid in the acetic acid aqueous solution is 0.5-1.5%, for example, it can be a range of one or any combination of 0.5%, 0.7%, 0.9%, 1.1%, 1.3%, and 1.5%.

[0062] Specifically, the mass ratio of chitosan to ammonium persulfate is 1:(0.03-0.07), for example, it can be one of 1:0.03, 1:0.04, 1:0.05, 1:0.06, 1:0.07 or any combination of both.

[0063] In some embodiments, the microporous concrete includes polypropylene fibers in the form of 0.5-2.5 parts by weight; for example, it may be a range of one or any combination of 0.5, 0.7, 0.9, 1.1, 1.3, 1.5, 1.7, 1.9, 2.1, 2.3, and 2.5 parts.

[0064] In this application, polypropylene fibers can improve the stability of the pore structure, thereby improving the porosity and mechanical properties of microporous concrete.

[0065] In some embodiments, the average length of the polypropylene fiber is 3-6 mm, for example, it can be a range of one or any two of 3 mm, 3.5 mm, 4 mm, 4.5 mm, 5 mm, 5.5 mm, and 6 mm; the average diameter is 5-15 μm, for example, it can be a range of one or any two of 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, and 15 μm.

[0066] In this application, the average length and average diameter of the polypropylene fibers are within the above-mentioned range, which is beneficial for uniform dispersion within the stable foam during the mixing process and for forming an effective "pore wall-fiber" micro-support structure at the pore interface during the molding and curing of microporous concrete, thereby better resisting the shrinkage stress caused by moisture evaporation.

[0067] In some implementations, at least one of the following (1)-(5) is satisfied: (1) The coarse aggregate is granite crushed stone and / or basalt crushed stone with an average particle size of 5-10 mm; (2) The fine aggregate is quartz sand with an average particle size of 1-2 mm; (3) The foaming agent is a protein-based foaming agent; (4) The air-entraining agent is a rosin thermal polymer air-entraining agent; (5) The cement is silicate cement.

[0068] Specifically, the protein foaming agent is an animal protein foaming agent; animal protein foaming agents can be obtained by purchasing commercially available products or by preparation methods known in the prior art.

[0069] Secondly, a method for preparing the aforementioned microporous concrete is provided, comprising the following steps: Preparation of dry mixture: Cement, fly ash, coarse aggregate, fine aggregate and modified hydroxyapatite powder are mixed evenly to obtain dry mixture; Preparation of slurry: Add cetearyl glucoside, air-entraining agent and water to the dry mixture, stir evenly to obtain slurry; Foam preparation: Foam is obtained by foaming with a foaming agent; Preparation of microporous concrete: Add foam to the slurry and stir evenly to obtain microporous concrete.

[0070] Specifically, in the step of preparing the dry mixture, the stirring speed is 60-80 rpm, for example, it can be a range of one or any two of 60 rpm, 62 rpm, 64 rpm, 66 rpm, 68 rpm, 70 rpm, 72 rpm, 74 rpm, 76 rpm, 78 rpm, and 80 rpm; the time can be 2-4 min, for example, it can be a range of one or any two of 2 min, 3 min, and 4 min.

[0071] Specifically, in the step of preparing the slurry, the stirring speed is 120-150 rpm, for example, it can be one or any combination of 120 rpm, 125 rpm, 130 rpm, 135 rpm, 140 rpm, 145 rpm, and 150 rpm; the time can be 3-5 min, for example, it can be one or any combination of 3 min, 4 min, and 5 min.

[0072] Specifically, the density of the foam is 35-45 g / L, for example, it can be a range of one or any combination of 35 g / L, 37 g / L, 39 g / L, 41 g / L, 43 g / L, and 45 g / L.

[0073] Specifically, in the step of preparing microporous concrete, the stirring speed is 40-100 rpm, for example, it can be a range of one or any two of 40 rpm, 45 rpm, 50 rpm, 55 rpm, 60 rpm, 65 rpm, 70 rpm, 75 rpm, 80 rpm, 85 rpm, 90 rpm, 95 rpm, and 100 rpm; the time is 2-3 minutes.

[0074] In some embodiments, the step of adding foam to the slurry is as follows: The foam is divided into a first foam and a second foam, with the volume of the first foam being 60-70% of the total foam volume. The second foam and the second silane coupling agent are mixed evenly to obtain the third foam; wherein the mass of the second silane coupling agent is 0.5-1% of the mass of the foam. Add the first foam to the slurry and stir evenly. Then add the third foam at a temperature of 20-35℃ and stir evenly to obtain microporous concrete.

[0075] In this application, the foam is added in two stages, which helps to avoid the merging and breaking of the foam caused by adding it all at once during the stirring process, resulting in a more uniform pore distribution. At the same time, the second-stage foam is premixed with the second silane coupling agent KH-560, which can enhance the interfacial bonding force between the foam and the slurry and further improve the stability of the pore structure.

[0076] Specifically, the second silane coupling agent is KH560.

[0077] Specifically, in the step of preparing the third foam, the stirring speed is 40-60 rpm, for example, it can be a range of one or any combination of 40 rpm, 45 rpm, 50 rpm, 55 rpm, 60 rpm; the time is 60-90 s.

[0078] Specifically, the stirring speed when the second foam is added is 80-100 rpm, for example, it can be one or any combination of 80 rpm, 85 rpm, 90 rpm, 95 rpm, 100 rpm.

[0079] In some embodiments, the microporous concrete comprises polypropylene fibers, and the method for preparing the microporous concrete includes the following steps: Preparation of dry mixture: Cement, fly ash, coarse aggregate, fine aggregate and modified hydroxyapatite powder are mixed evenly to obtain dry mixture; Preparation of slurry: Add cetearyl glucoside, air-entraining agent and water to the dry mixture, stir evenly to obtain slurry; Foam preparation: The foaming agent and polypropylene fiber are mixed and then foamed to obtain foam; Preparation of microporous concrete: Add foam to the slurry and stir evenly to obtain microporous concrete.

[0080] In this application, polypropylene fibers are added during the foam preparation process. The polypropylene fibers are uniformly dispersed with the foam. When the foam is formed into pores, the polypropylene fibers are distributed at the pore interface to form a "pore wall-fiber" micro-support structure. The micro-support structure can directly resist the pore shrinkage stress caused by water evaporation during the curing process of microporous concrete, reduce pore collapse and merging, and inhibit the expansion of microcracks at the pore interface when under stress, thereby improving the porosity and mechanical properties of microporous concrete.

[0081] Example 1 This embodiment provides a microporous concrete comprising the following components in parts by weight: 75 parts silicate cement, 25 parts fly ash, 125 parts coarse aggregate, 190 parts fine aggregate, 0.25 parts cetearyl glucoside microcapsules, 6 parts modified hydroxyapatite powder, 0.65 parts animal protein foaming agent, 0.016 parts rosin thermal polymer air-entraining agent, 1.5 parts polypropylene fiber, and 52 parts water. The coarse aggregate is granite crushed stone with an average particle size of 8 mm; the fine aggregate is quartz sand with an average particle size of 1.5 mm; the weight of the cetearyl glucoside microcapsules is based on the weight of cetearyl glucoside. The preparation method of modified hydroxyapatite powder includes the following steps: Hydroxyapatite powder was dispersed in a tannic acid aqueous solution with a mass concentration of 3 mg / mL. After adjusting the pH of the system to 8.3, the mixture was stirred at 50°C for 3 h. The product obtained from the reaction was filtered, washed, and dried at 70°C to obtain tannic acid modified hydroxyapatite. Tannic acid-modified hydroxyapatite was dispersed in a sodium silicate aqueous solution with a molar concentration of 0.3 mol / L and stirred at 30°C for 1.5 h. After adjusting the pH of the system to 6.5 with dilute hydrochloric acid, the reaction was continued for 2 h. Then, a first silane coupling agent solution was added, and the reaction was stirred at 30°C for 0.5 h. The product obtained from the reaction was filtered, washed, and dried at 90°C to obtain modified hydroxyapatite. The mass-volume ratio of hydroxyapatite to tannic acid aqueous solution is 1g:75mL; The mass-to-volume ratio of tannic acid-modified hydroxyapatite and sodium silicate aqueous solution was 1 g: 45 mL; The mass of the first silane coupling agent is 10% of the mass of sodium silicate; The preparation method of the first silane coupling agent solution includes the following steps: γ-aminopropyltriethoxysilane was added to an ethanol / water solution, and the pH of the system was adjusted to 4.5 with dilute hydrochloric acid. The solution was then stirred and hydrolyzed at 30°C for 30 min to obtain a first silane coupling agent solution. The volume ratio of γ-aminopropyltriethoxysilane to the ethanol / water solution was 1:7, and the volume percentage of ethanol in the ethanol / water solution was 50%. The preparation method of cetearyl glucoside microcapsules includes the following steps: Cetearyl glucoside is heated to 60°C and melted to form a core material solution; Add 15 parts by weight of chitosan to 600 parts by weight of 1% acetic acid aqueous solution, dissolve, then add 15 parts by weight of polyethylene glycol diacrylate and 0.75 parts by weight of ammonium persulfate, stir evenly to form a wall material solution. The core material solution was added dropwise to the wall material solution, and sheared and emulsified at 2500 rpm for 10 min to obtain an emulsion. The emulsion was placed in a microwave reactor and irradiated at 350 W and 65 °C for 25 min. The obtained product was cooled, centrifuged, washed and dried to obtain cetearyl glucoside microcapsules with an average particle size of 5 μm. The manufacturer of the animal protein foaming agent is Liaocheng Jiukun Building Materials Co., Ltd., and the model number is JK-FP30. The polypropylene fibers have an average length of 5 mm and an average diameter of 10 μm.

[0082] This embodiment provides a method for preparing microporous concrete, including the following steps: Preparation of dry mixture: Cement, fly ash, coarse aggregate, fine aggregate and modified hydroxyapatite powder are added to a mixer in proportion and stirred at 70 rpm for 3 minutes to obtain dry mixture; Preparation of slurry: Add cetearyl glucoside microcapsules, rosin thermal polymer air-entraining agent and water to the dry mixture, and stir at 135 rpm for 3 min to obtain slurry; Foam preparation: Animal protein foaming agent and polypropylene fiber are added to high-pressure foaming agent to obtain foam with a density of 40 g / L; Preparation of microporous concrete: The foam is divided into a first foam and a second foam, with the volume of the first foam being 65% of the total foam volume and the volume of the second foam being 35% of the total foam volume; The second foam and silane coupling agent KH-560 were mixed evenly to obtain the third foam; wherein the mass of the second silane coupling agent was 0.75% of the mass of the foam. The first foam was added to the slurry at a stirring speed of 50 rpm and stirred for 75 seconds. Then, the third foam was added at a slurry temperature of 30℃ and a stirring speed of 90 rpm and stirred for 75 seconds to obtain microporous concrete.

[0083] Example 2 This embodiment provides a microporous concrete, which differs from Embodiment 1 in that the preparation method of the modified hydroxyapatite is different. The preparation method of the modified hydroxyapatite in this embodiment is as follows: Hydroxyapatite powder was dispersed in an aqueous solution of tannic acid with a mass concentration of 3 mg / mL. After adjusting the pH of the system to 8.3, the mixture was stirred at 50°C for 3 hours. The product obtained from the reaction was filtered, washed, and dried at 70°C to obtain modified hydroxyapatite. The mass-to-volume ratio of hydroxyapatite to tannic acid aqueous solution is 1 g: 75 mL.

[0084] Example 3 This embodiment provides a microporous concrete, which differs from Embodiment 1 in that the preparation method of the modified hydroxyapatite is different. The preparation method of the modified hydroxyapatite in this embodiment is as follows: Hydroxyapatite powder was dispersed in a tannic acid aqueous solution with a mass concentration of 3 mg / mL. After adjusting the pH of the system to 8.3, the mixture was stirred at 50°C for 3 h. The product obtained from the reaction was filtered, washed, and dried at 70°C to obtain tannic acid modified hydroxyapatite. Tannic acid-modified hydroxyapatite was dispersed in a sodium silicate aqueous solution with a molar concentration of 0.3 mol / L, stirred at 30°C for 1.5 h, and the pH of the system was adjusted to 6.5 with dilute hydrochloric acid. The reaction was continued for 2 h. The product obtained was filtered, washed, and dried at 90°C to obtain modified hydroxyapatite. The mass-volume ratio of hydroxyapatite to tannic acid aqueous solution is 1g:75mL; The mass-to-volume ratio of tannic acid-modified hydroxyapatite and sodium silicate aqueous solution was 1 g: 45 mL.

[0085] Example 4 This embodiment provides a microporous concrete, which differs from Embodiment 1 in that: cetearyl glucoside is used instead of cetearyl glucoside microcapsules; that is, the cetearyl glucoside in this embodiment has no coating layer on its surface.

[0086] Example 5 This embodiment provides a microporous concrete, which differs from Embodiment 1 in that it does not contain added polypropylene fibers.

[0087] Example 6 This embodiment provides a microporous concrete, which differs from Embodiment 1 in that the weight proportions of each component in the microporous concrete are different. The microporous concrete in this embodiment includes the following components in parts by weight: 60 parts silicate cement, 20 parts fly ash, 100 parts coarse aggregate, 180 parts fine aggregate, 0.1 parts cetearyl glucoside microcapsules, 3 parts modified hydroxyapatite powder, 0.5 parts animal protein foaming agent, 0.01 parts rosin thermal polymer air-entraining agent, 0.5 parts polypropylene fiber, and 45 parts water.

[0088] Example 7 This embodiment provides a microporous concrete, which differs from Embodiment 1 in that the weight parts of each component in the microporous concrete are different. The microporous concrete in this embodiment includes the following components in parts by weight: 90 parts silicate cement, 30 parts fly ash, 150 parts coarse aggregate, 200 parts fine aggregate, 0.5 parts cetearyl glucoside microcapsules, 10 parts modified hydroxyapatite powder, 0.8 parts animal protein foaming agent, 0.024 parts rosin thermal polymer air-entraining agent, 2.5 parts polypropylene fiber, and 60 parts water.

[0089] Comparative Example 1 This comparative example provides a microporous concrete that differs from Example 1 in that it does not contain cetearyl glucoside microcapsules.

[0090] Comparative Example 2 This comparative example provides a microporous concrete, which differs from Example 1 in that no modified hydroxyapatite is added.

[0091] Comparative Example 3 This comparative example provides a microporous concrete that differs from Example 1 in that it does not contain modified hydroxyapatite and cetearyl glucoside microcapsules.

[0092] Comparative Example 4 This comparative example provides a microporous concrete, which differs from Example 1 in that hydroxyapatite powder is used instead of modified hydroxyapatite powder; that is, the hydroxyapatite in this comparative example has not been modified.

[0093] Comparative Example 5 This comparative example provides a microporous concrete comprising the following components in parts by weight: 75 parts silicate cement, 25 parts fly ash, 125 parts coarse aggregate, 190 parts fine aggregate, 0.016 parts rosin thermal polymer air-entraining agent, and 52 parts water.

[0094] This comparative example provides a method for preparing microporous concrete, including the following steps: Preparation of dry mixture: Cement, fly ash, coarse aggregate, fine aggregate and modified hydroxyapatite powder are added to a mixer in proportion and stirred at 70 rpm for 3 minutes to obtain dry mixture; Preparation of microporous concrete: Add rosin thermal polymer air-entraining agent and water to the dry mixture, and stir at 135 rpm for 3 min to obtain microporous concrete.

[0095] Performance testing The microporous concrete obtained from the examples and comparative examples was poured into molds to obtain test blocks (20 test blocks were prepared for each example and comparative example; taking one example, 20 test blocks were prepared for Example 1, of which 5 were used for porosity testing, 5 for average pore size testing, 5 for compressive strength testing, and the remaining 5 for flexural strength testing. The average value of 5 test blocks was taken for each test, and the size of the test blocks was prepared according to the testing requirements). The test blocks were cured in an environment with a temperature of 20±2℃ and a relative humidity of not less than 95% for 28 days. The performance of the cured test blocks was then tested, and the testing methods are as follows: (1) Porosity: The effective porosity test method is specified in Appendix A of CJJ / T 253-2016. After curing, the specimen is dried to constant weight, immersed in water for 24 h, and then the dry mass of the saturated surface and the buoyant weight in water are measured to calculate the porosity. The formula for calculating the effective porosity is:

[0096] In the formula, m1 is the buoyant weight in water, m2 is the dry weight at saturation, V is the volume of the test block, and ρ w 1 g / cm 3 .

[0097] (2) Average pore size: The test was conducted in accordance with GB / T 21650.1-2008 "Determination of pore size distribution and porosity of solid materials by mercury porosimetry and gas adsorption method - Part 1: Mercury porosimetry". Samples with a size of approximately 1 cm × 1 cm × 1 cm were drilled from the center of the cured test block and tested using a mercury porosimetry instrument. The maximum pressure was 200 MPa (corresponding to a minimum pore size of approximately 5 nm). Five test blocks were taken for each group (each example or comparative example), and samples from three different locations were tested on each test block. The results were taken as the arithmetic mean. It should be noted that the result obtained by mercury porosimetry is the throat diameter (inlet pore diameter) of the connected pores, not the maximum diameter of the pore cavity.

[0098] (3) Compressive strength: Tested according to JG / T 266-2011 "Foamed Concrete". 100 mm × 100 mm × 100 mm cube specimens were used. The loading speed of the press was 0.8 kN / s (or 0.08 MPa / s). Five specimens were used in each group, and the arithmetic mean was taken. (4) Flexural strength: The test was conducted in accordance with JG / T 266-2011 "Foamed Concrete". 100 mm × 100 mm × 400 mm prism specimens were used. The four-point bending method was used with a span of 300 mm and a loading speed of 0.08 kN / s. Five specimens were used in each group, and the arithmetic mean was taken.

[0099] The test results are shown in Table 1.

[0100] Table 1

[0101] As shown in Table 1, the microporous concrete of this application has a porosity greater than 35%, an average pore size less than 40 μm, a compressive strength greater than 19 MPa, and a flexural strength greater than or equal to 3.5 N / mm². 2 This demonstrates that the microporous concrete of this application possesses both high porosity and mechanical properties.

[0102] The experimental data from Examples 1-3 and Comparative Example 4 show that modifying hydroxyapatite can optimize the interfacial bonding force between the modified hydroxyapatite and the pores, reduce pore collapse, and improve the porosity and mechanical properties of microporous concrete.

[0103] As can be seen from the descriptions of Examples 1 and 4, a coating layer is provided on the surface of cetearyl glucoside. The coating layer can enhance the sustained effect of cetearyl glucoside and modified hydroxyapatite, effectively improving the porosity and mechanical properties of microporous concrete.

[0104] As can be seen from the descriptions of Examples 1 and 5, when polypropylene fibers are added to microporous concrete, the polypropylene fibers are distributed at the pore interface when the foam forms pores in the microporous concrete slurry, forming a microscopic support structure of pore wall-fiber, thereby improving the porosity and mechanical properties of the microporous concrete.

[0105] The experimental data from Example 1 and Comparative Examples 1-3 show that the lack of modified hydroxyapatite and / or cetearyl glucoside leads to a decrease in the porosity and mechanical properties of microporous concrete.

[0106] The experimental data from Examples 1-7 and Comparative Example 5 show that Comparative Example 5 is a traditional concrete formula. Traditional concrete has low porosity and mechanical properties, which makes it difficult to meet the requirements of seawall structures.

[0107] Finally, it should be noted that the above embodiments are used to illustrate the technical solutions of this application and not to limit the scope of protection of this application. Although this application has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of this application without departing from the substance and scope of the technical solutions of this application.

Claims

1. A microporous concrete, characterized in that, The composition comprises the following components in parts by weight: 60-90 parts cement, 20-30 parts fly ash, 100-150 parts coarse aggregate, 180-200 parts fine aggregate, 0.1-0.5 parts cetearyl glucoside, 3-10 parts modified hydroxyapatite, 0.5-0.8 parts foaming agent, 0.01-0.024 parts air-entraining agent, and 45-60 parts water; wherein the modifier of the modified hydroxyapatite includes tannic acid.

2. The microporous concrete as described in claim 1, characterized in that, The preparation method of the modified hydroxyapatite includes the following steps: Hydroxyapatite was added to an aqueous solution of tannic acid, and the pH was adjusted to 8-8.5 with a pH adjuster. The mixture was stirred at 40-60℃ for 2-4 hours. The product obtained from the reaction was filtered, washed, and dried to obtain modified hydroxyapatite. The mass-volume ratio of hydroxyapatite to the aqueous solution of tannic acid was 1 g: (50-100) mL.

3. The microporous concrete as described in claim 1, characterized in that, The modifier of the modified hydroxyapatite further includes sodium silicate; the preparation method of the modified hydroxyapatite includes the following steps: Hydroxyapatite was added to an aqueous solution of tannic acid, and the pH was adjusted to 8-8.5 with a pH adjuster. The mixture was stirred and reacted at 40-60℃ for 2-4 hours. The product obtained from the reaction was filtered, washed, and dried to obtain tannic acid-modified hydroxyapatite. Tannic acid-modified hydroxyapatite was added to an aqueous solution of sodium silicate and stirred at 25-40°C for 1-2 hours. The pH was adjusted to 6.0-7.0 with a pH adjuster, and the reaction was continued for 1-2 hours. The product obtained from the reaction was filtered, washed, and dried to obtain modified hydroxyapatite. The mass-to-volume ratio of hydroxyapatite to tannic acid aqueous solution is 1 g: (50-100) mL. The mass-to-volume ratio of tannic acid-modified hydroxyapatite and sodium silicate aqueous solution is 1 g: (30-60) mL.

4. The microporous concrete as described in claim 3, characterized in that, The modifier of the modified hydroxyapatite further includes a silane coupling agent; the preparation method of the modified hydroxyapatite includes the following steps: Hydroxyapatite was added to an aqueous solution of tannic acid, and the pH was adjusted to 8-8.5 with a pH adjuster. The mixture was stirred and reacted at 40-60℃ for 2-4 hours. The product obtained from the reaction was filtered, washed, and dried to obtain tannic acid-modified hydroxyapatite. Tannic acid-modified hydroxyapatite was added to an aqueous solution of sodium silicate and stirred at 25-40°C for 1-2 hours. After adjusting the pH to 6-7 with a pH adjuster, the reaction was continued for 1-2 hours. Then, a first silane coupling agent solution was added and the reaction was stirred at 25-40°C for 0.5-1 hours. The product obtained from the reaction was filtered, washed, and dried to obtain modified hydroxyapatite. The mass-to-volume ratio of hydroxyapatite to tannic acid aqueous solution is 1 g: (50-100) mL. The mass-to-volume ratio of tannic acid-modified hydroxyapatite and sodium silicate aqueous solution is 1 g: (30-60) mL; The mass of the first silane coupling agent is 5-15% of the mass of sodium silicate.

5. The microporous concrete as described in claim 4, characterized in that, The first silane coupling agent is at least one of aminosilane coupling agents and epoxysilane coupling agents; And / or, the preparation method of the first silane coupling agent solution is as follows: add the first silane coupling agent to an ethanol / water solution, adjust the pH to 4-5 with a pH adjuster, and stir at 25-35℃ for 30-40 min to obtain the first silane coupling agent solution, wherein the volume ratio of ethanol to water is 1:(5-10).

6. The microporous concrete as described in claim 1, characterized in that, The cetearyl glucoside has a coating layer on its surface, the coating layer comprising polyethylene glycol diacrylate and chitosan.

7. The microporous concrete as described in claim 1, characterized in that, The microporous concrete includes polypropylene fibers, wherein the polypropylene fibers are present in a weight ratio of 0.5 to 2.5 parts.

8. The microporous concrete as described in claim 1, characterized in that, Satisfy at least one of the following (1)-(5): (1) The coarse aggregate is granite crushed stone and / or basalt crushed stone with an average particle size of 5-10 mm; (2) The fine aggregate is quartz sand with an average particle size of 1-2 mm; (3) The foaming agent is a protein-based foaming agent; (4) The air-entraining agent is a rosin thermal polymer air-entraining agent; (5) The cement is silicate cement.

9. A method for preparing microporous concrete as described in any one of claims 1-7, characterized in that, Includes the following steps: Cement, fly ash, coarse aggregate, fine aggregate, and modified hydroxyapatite powder are mixed evenly to obtain a dry mixture; Add cetearyl glucoside, air-entraining agent and water to the dry mixture, stir well to obtain slurry; Foam is obtained by foaming with a foaming agent; Add foam to the slurry and stir evenly to obtain microporous concrete.

10. The method for preparing microporous concrete as described in claim 9, characterized in that, The step of adding foam to the slurry is as follows: The foam is divided into a first foam and a second foam, with the volume of the first foam being 60-70% of the total foam volume. The second foam and the second silane coupling agent are mixed evenly to obtain the third foam; wherein the mass of the second silane coupling agent is 0.5-1% of the mass of the foam. Add the first foam to the slurry and stir evenly. Then add the third foam at a temperature of 20-35℃ and stir evenly to obtain microporous concrete.